What kind of coffee do you drink? An investigation on effects of eight different extraction methods. (February 2019) - Angeloni, Giulia; Guerrini, Lorenzo; Masella, Piernicola; Bellumori, Maria; Daluiso, Selvaggia; Parenti, Alessandro; Innocenti, Marzia
Abstract: The chemical composition of brewed coffee depends on numerous factors: the beans, post-harvest processing and, finally, the extraction method. In recent decades, numerous coffee-based beverages, obtained using different extraction techniques have entered the market. This study characterizes and compares eight extraction coffee methods from a chemical-physical point of view, starting from the same raw material. Specifically, three types of Espresso, Moka, French Press, and 3 filter coffee that for the first time are reported in the scientific literature Cold Brew, V60, and Aeropress are compared. Physical measurements included the quantification of total dissolved solids, density, pH, conductivity, and viscosity. Chemical analyses identified 15 chlorogenic acids (CGAs): six caffeoylquinic acids, one p-Coumaroylquinic acid, one Feruloylquinic Acid, four Caffeoylquinic lactones, and three Dicaffeoylquinic acids. Maximum caffeine and CGA concentrations were found in Espresso coffees, while Moka and filtered coffees were three to six times less concentrated. The classic Espresso method was most efficient for caffeine and CGA recovery, with a yield almost double that of other methods. Per-cup caffeine and CGAs were higher in Cold Brew than Espresso coffees, as a function of the volume of beverage, which ranged from 30 mL (for espresso) to 120 mL (for filtered coffees). In light of these results, it is not possible to establish how many cups of coffee can be consumed per day without exceeding the recommended doses, since according to the applied brewing method, the content of the bioactive substances varies considerably. Graphical abstract: Unlabelled Image Highlights: Numerous coffee beverages obtained using different extraction have entered the market This study characterizes and compares eight brewing methods The qualitative profile of bioactive substances was detected by HPLC-DAD The study informs on concentrations and on per-cup caffeine and chlorogenic acids content